Modification of Hyaluronan by Heavy Chains of Inter-α-Inhibitor in Idiopathic Pulmonary Arterial Hypertension - Lauer, Mark E. (American Society for Biochemistry and Molecular Biology, 2014)
We previously reported an altered hyaluronan (HA) metabolism in idiopathic pulmonary arterial hypertension (IPAH) lung tissue and cultured smooth muscle cells. Hyaluronan was present in the smooth muscle cell layer surrounding the pulmonary vasculature and in plexigenic lesions. Additionally, cultured pulmonary artery smooth muscle cells produced spontaneous HA “cable” structures, without additional stimuli, that were leukocyte-adhesive. We now present evidence that the HA that accumulates in IPAH plexigenic lesions is a pathological form of HA in which heavy chains (HCs) from the serum-derived proteoglycan inter-α-inhibitor are covalently attached to the HA backbone to form a pathological HC-HA complex. CD45-positive leukocytes were identified within these HC-HA matrices. Elevated mRNA levels of the enzyme that transfers HCs to HA, known as tumor necrosis factor-stimulated gene 6, were detected in IPAH lung tissue.